دور الاستخدامات التكنولوجية الحديثة في تحسين جودة الخدمات الإدارية، دراسة ميدانية - غاي, فاطمة (جامعة الوادي university of eloued, 2022)
تهدف هذه الدراسة إلى إبراز دور الاستخدامات التكنولوجية الحديثة في تحسين جودة الخدمات بمؤسسة اتصالات الجزائر، بولاية الطارف، ذلك بالاعتماد على المنهج الوصفي التحليلي، وعلى أداة الاستمارة بالمقابلة، التي وزعت على عينة قصدية متكونة من 50 عاملا داخل المؤسسة مجال الدراسة، حيث تم التوصل لنتائج أساسية نوجزها فيما يلي: للاستخدامات التكنولوجية الحديثة بالمؤسسة مجال الدراسة دور إيجابي وفعال في تحسين جودة الخدمات الإدارية. كما تساهم في تحقيق تمكين تكنولوجي للعمال. إضافة لذلك توصلت الدراسة إلى أن الاستخدام التكنولوجي الحديث يساهم في تحقيق المرونة والفعالية أثناء تأدية المهام بالمؤسسة مجال الدراسة. This study aims to highlight the role of modern technological uses in improving the quality of services at Algeria Telecom, El Tarf, by relying on the descriptive analytical method, and on the interview form tool, which was distributed to a deliberate sample consisting of 50 workers within the institution, the field of study, where the results were reached. We summarize the basics below: The modern technological uses of the institution, the field of study, have a positive and effective role in improving the quality of administrative services. It also contributes to achieving technological empowerment for workers. In addition, the study concluded that the use of modern technology contributes to achieving flexibility and effectiveness during the performance of tasks in the institution, the field of study.
مقال
Keywords: الاستخدام التكنولوجي، تكنولوجيا الإعلام، تكنولوجيا الاتصال، الجودة، الخدمات، جودة الخدمات، المؤسسة